SPECIFICITY OF INTERNAL MIGRATION IN THE REPUBLIC OF DAGESTAN CORDING TO THE STATISTICS OF THE POPULATION OF THE URBAN SETTLEMENT OF SEMENDER, MAKHACHKALA - A. A. Abdullaev (Современная наука и инновации)
The article is devoted to quantitative and qualitative analysis of some socio-demographic characteristics of the population of the village of Semender (Makhachkala). The author of the article sets the task of determining the real share of migrants in the structure of the settlement, their territorial and ethnic origin.